Blackberry Leaves as New Functional Food? Screening Antioxidant, Anti-Inflammatory and Microbiological Activities in Correlation with Phytochemical Analysis - Magdalena Paczkowska-Walendowska; Anna Gościniak; Daria Szymanowska; Dominik Szwajgier; Ewa Baranowska-Wójcik; Piotr Szulc; Dagna Dreczka; Marek Simon; Judyta Cielecka-Piontek (MDPI AG, 2021)
Blackberry fruits are recognized as functional foods while blackberry leaves are outside this classification and they also contain active compounds with health-promoting potential. Therefore, the aim of this study was the phytochemical analysis of blackberry leaves of varieties (Chester, Loch Ness, Loch Tay and Ruczaj) and screening of their biological activity (antioxidant potential, possibility of inhibition of enzymes, anti-inflammatory and microbial activity). The following compounds from selected groups: phenolic acids (caffeic acid, ellagic acid, gallic acid, syringic acid), flavonols (quercetin, kaempferol) and their glycosides (rutin, isoquercetin, hyperoside) and flavon-3-ols (catechin, epicatechin) were chromatographically determined in the aqueous and hydroalcoholic leaves extracts. All tested blackberry leaves extracts showed antioxidant effects, but the highest compounds content (TPC = 101.31 mg GAE/g) and antioxidant activity (e.g., DPPH IC50 = 57.37 μg/mL; ABTS IC50 = 24.83 μg/mL; CUPRAC IC50 = 62.73 μg/mL; FRAP IC50 = 39.99 μg/mL for hydroalcoholic extracts) was indicated for the Loch Tay variety. Blackberry leaf extracts' anti-inflammatory effect was also exceptionally high for the Loch Tay variety (IC50 = 129.30 μg/mL), while leaves extracts of the Loch Ness variety showed a significant potential for microbial activity against Lactobacillus spp. and Candida spp. Summarizing, the best multidirectional pro-health effect was noted for leaves extracts of Loch Tay variety.